OPTIMIZATION OF FREQUENCY FILTERING IN RANDOM ACCESS JPEG LIBRARY - Radziszewski, Michał; Alda, Witold (Computer Science, 2013)
In the paper we present a method of direct access to single blocks of JPEG files whichcontain textures, with on-the-fly decompression. Anisotropic, adaptive filtering is applied inorder to minimize visual defects appearing mainly on blocks borders. Main purpose of themethod is to enable fast extraction of only these parts of an entire image which are currentlyneeded and not to keep whole decompressed texture in the main memory. This approachenables effective usage of high quality textures with low memory consumption. It’s benefitsare mainly demonstrated in rendering complex 3D scenes using nondeterministic ray-tracingalgorithm. The algorithms have been encapsulated into DLL and static library.